2012
DOI: 10.2478/v10239-012-0018-z
|View full text |Cite
|
Sign up to set email alerts
|

On the Specifics of Podzols in Mountain Areas

Abstract: O Specyfice Bielic Górskich

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The 3 rd order, podzolic soils (gleby bielicoziemne), covers the soils with a spodik horizon, merged in one soil type -gleby bielicowe, closely related to Podzols of WRB2015. The soil type includes several subtypes related in the majority to redoximorphic features and various organic horizons developed at the soil surface (Chodorowski 2009, Kaba³a et al 2012, Waroszewski et al 2013. In Polish tradition, podzolic soils having and lacking topsoil A horizon are distinguished into separate units, a fact which also influences the number of subtypes and their combinations in SGP6.…”
Section: Classification Schemementioning
confidence: 99%
“…The 3 rd order, podzolic soils (gleby bielicoziemne), covers the soils with a spodik horizon, merged in one soil type -gleby bielicowe, closely related to Podzols of WRB2015. The soil type includes several subtypes related in the majority to redoximorphic features and various organic horizons developed at the soil surface (Chodorowski 2009, Kaba³a et al 2012, Waroszewski et al 2013. In Polish tradition, podzolic soils having and lacking topsoil A horizon are distinguished into separate units, a fact which also influences the number of subtypes and their combinations in SGP6.…”
Section: Classification Schemementioning
confidence: 99%
“…Formation of mature Podzol requires usually 2000-5000 years (Egli et al, 2001;Mokma et al, 2004;Righi et al, 1999;Sauer et al, 2008), but first morphological features of podzolization already are observed after 100-200 years (Kabala et al, 2011;Kabala et al, 2012;Mavris et al, 2011). In the homogeneous materials (e.g.…”
Section: Introductionmentioning
confidence: 97%
“…Formation of Podzols in the mountain areas is mainly driven by cool and humid climate conditions, topography, as well as specific vegetation [1,3,[6][7][8][9][10][11][12][13][14][15]. It is widely accepted that coniferous forests promote the formation of proper Podzols [6].…”
Section: Introductionmentioning
confidence: 99%